1980
DOI: 10.1159/000122974
|View full text |Cite
|
Sign up to set email alerts
|

Participation of the Dorsal Hippocampus in the Glucocorticoid Feedback Effect on Adrenocortical Activity

Abstract: The feedback effect of systemically administered dexamethasone on basal plasma corticosterone levels and on adrenocortical responses to ether plus skin incision stress were studied in intact rats and in animals with bilateral dorsal or ventral hippocampectomy or fimbria section. It was found that in rats with ventral hippocampectomy or fimbria section, the degree of the feedback was similar to that in intact rats. However, in animals with dorsal hippocampectomy, the inhibitory effect of dexamethasone on basal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
78
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 194 publications
(82 citation statements)
references
References 21 publications
4
78
0
Order By: Relevance
“…Ether was used to anaesthetize the animals to collect the blood samples by using the technique of Feldman and Conforti to avoid stress. 21) Drug Terminalia chebula, Terminalia belerica and Emblica o‹cinalis ( Table 1) were collected and authenticated by the Chief Botanist, Tamil Nadu Medicinal Plant Farms and Herbal Medicine Corporation (TAMPCOL) Ltd, Chennai, India. The seedless fruits were dried under shade and made intoˆne powder.…”
Section: Experimental Groupsmentioning
confidence: 99%
“…Ether was used to anaesthetize the animals to collect the blood samples by using the technique of Feldman and Conforti to avoid stress. 21) Drug Terminalia chebula, Terminalia belerica and Emblica o‹cinalis ( Table 1) were collected and authenticated by the Chief Botanist, Tamil Nadu Medicinal Plant Farms and Herbal Medicine Corporation (TAMPCOL) Ltd, Chennai, India. The seedless fruits were dried under shade and made intoˆne powder.…”
Section: Experimental Groupsmentioning
confidence: 99%
“…Ether was used to anaesthetize the animals to collect the blood samples by using the technique of Feldman and Conforti 18) to avoid stress. This procedure was conducted during the morning hours between 08.00-10.00 a.m. to avoid circadian influences.…”
Section: Experimental Groupsmentioning
confidence: 99%
“…In adrenalectomized rats, administration of the type II glucocorticoid receptor agonist RU 28362 has been shown to reduce CRF gene expression in the PVN , whereas in intact rats, dexamethasone treatment reduces both basal and stress-stimulated levels of CRF mRNA (Lightman and Young, 1989), with the PVN implicated as a key site of dexamethasone action (Harbuz and Lightman, 1989). The hippocampus, an area that contains substantial concentrations of both type I and type II glucocorticoid receptor subtypes (McEwen et al, 1968;Reul and De Kloet, 1985), has been shown to play a role in the CORT-mediated containment of HPA responses (Jacobson and Sapolsky, 1991;Feldman and Conforti, 1980). As suggested above, inhibitory inputs from the hippocampus to the PVN (Herman et al, 1996) may be enhanced in NRS compared with SRS rats.…”
Section: Why Are the Nrs Rats Stress-nonresponsive And Deficient In Cmentioning
confidence: 99%